ORIGINAL ARTICLE - Ciprian Băcilă; Mihaela Tănase; Rareş Clopoţel (Psihiatru.ro)
Admissions of psychoactive substance users in Romanian psychiatric hospitals (2018-2021) Suicidology in Romania – traditions and future perspectives Medical and legal safety measures for people with psychiatric pathology and dangerous behavior